Making Scholarship Public: Collaboration and Interdisciplinarity in Early Modern Studies - Yachnin, Paul (Renaissance and Reformation / Renaissance et Réforme, 2014)
How can collaborative, interdisciplinary research on early modern Europe expand the reach of the humanities beyond the academy? In what ways could such a “public turn” enhance the effectiveness of humanities research and teaching? This essay recounts how a number of large, interdisciplinary projects in which the author has been centrally involved grew from scattered intuitions toward collective clarity; how they gathered people from different disciplines around shared questions and changed the ways participants saw their own work; how they enabled students and postdocs to grow as original thinkers by taking part in collaborative research; and how large-scale research that asks big questions might be able to build bridges between the academy and the multiple publics in Canada and beyond in ways that enhance both the university and society.